The study of clinical profile of severe dengue in children - A., Vinaykumar S.; Chandrasekhar, Gouli; S., Vinaykumar (International Journal of Contemporary Pediatrics, 2024)
Background: Dengue fever is one of the most important vectors borne viral diseases, causing the significant burden due to high admissions and mortality in southern parts of India. Early detection and early intervention of sickness can reduce this burden for which we should know the clinical features and other parameter in dengue so that mortality rate can be reduced. Methods: It was a retrospective single center study which included patients admitted to department of pediatrics from a period of October 2022 to November 2023. A total of 30 cases of severe dengue admitted in a span of 6 months. A detailed clinical and laboratory data was recorded in a questionnaire format which was analyzed using statistical tool. Results: Among 30 cases of severe dengue the most common clinical feature was shock (53%), hepatitis (36%), clinical fluid accumulation (33%), mucosal bleeding (26%) and ARDS (165). Severe dengue was frequently found in the range of white cell count 1000-4000/ul and platelet count 12000-50000/ul. Conclusions: The key to the management of severe dengue illness lies in the in-depth knowledge of clinical manifestation among children. Thus, it is important to be aware of warning signs and varied presentations of severe dengue so that there will be accurate management of in resource limited setups.